Pengaruh Senam Dismenore Terhadap Penurunan Nyeri Haid Pada Remaja Putri SMPN 03 Pabuaran Kabupaten Purwakarta - Dian Fitriyani; Ediyono, Suryo; Susanti, Cici; Rahmawati (Bunda Edu-Midwifery Journal (BEMJ), 2025)
Menstruation or or coming months is a physiological change in women that occurs periodically and is influenced by reproductive hormones, starting from menarche to menopause (Syafrudin, 2011). Menstruation is a physiological change in a woman's body that occurs regularly and is experienced every month on a regular basis. The brain releases reproductive hormones which facilitate the ovaries to release the hormones estrogen and progesterone. These two hormones will ripen the egg so that menstruation or pregnancy occurs if fertilization occurs (Anwar et al, 2014). Objective: To identify the effect of dysmenorrhea exercise on reducing dysmenorrhea in female adolescents at SMPN 3 Pabuaran. Methods: This research is a type of pre-experimental research with a Two Group Pretest and Posttest design approach in the control and intervention groups. The research population was all young girls at SMPN 3 Pabuaran Subang Regency in August-September 2022 with a total of 135 respondents, with a total sample of 30 respondents who were taken using an accidental sampling technique. Results: The results of this study showed that the mean value before doing menorrhoea exercise was 5.4667 with a standard deviation of 0.51640 and a standard error of 0.13333. while the mean value after doing dimenorrhoea is 2.8000 with a standard deviation of 0.41404 and a standard error of 0.10690. Based on the results of the Independent T-Test statistical test, it was obtained a P Value of 0.000 <0.050, so it can be concluded that there is an effect of doing menorrhoea exercise on reducing menstrual pain in adolescents. Conclusion: Based on the results of the analysis that has been carried out, there is an effect of dysmenorrhea exercise on reducing menstrual pain by P 0.001 < 0.050. Suggestion: It is recommended for young women who are menstruating to do physical exercise such as dysmenorrhea gymnastics to reduce excess pain during menstruation.